Hair Growth Defects in Insig-Deficient Mice Caused by Cholesterol Precursor Accumulation and Reversed by Simvastatin - Evers, Bret M. (2010)
Insig-1 and Insig-2, two closely related proteins, are essential for feedback inhibition of cholesterol biosynthesis. Here, we characterized a line of epidermal-specific, Insig-double knockout (Epi-Insig-DKO) mice lacking both Insigs in epidermis. At birth, Epi-Insig-DKO mice were indistinguishable from control littermates, but thereafter they failed to thrive and died before 6 weeks of age. By 14 days of age, 100% of Epi-Insig-DKO mice exhibited defects in hair growth along with other skin abnormalities, including hyperkeratosis. Hair follicles in Epi-Insig-DKO mice developed normally through postnatal day 7, but they failed to progress to later stages and thus exhibited defects in postnatal hair cycling. Insig deficiency caused a marked buildup of cholesterol precursors in skin associated with a marked increase in 3-hydroxy-3-methylglutaryl coenzyme A reductase protein. Topical treatment of Epi-Insig-DKO mice with simvastatin, an inhibitor of reductase, reduced sterol precursors in skin and corrected the hair and skin defects. We conclude that Insig deficiency in skin causes accumulation of cholesterol precursors, and this impairs normal hair development. These findings have implications for several human genetic diseases in which mutations in cholesterol biosynthetic enzymes lead to accumulation of sterol precursors and multiple cutaneous abnormalities.